Does pre-surgical central modulation of pain influence outcome after total knee replacement? A systematic review. Issue 2 (February 2016) - Baert, I.A.C.; Lluch, E.; Mulder, T.; Nijs, J.; Noten, S.; Meeus, M.
Summary: The aim of this study is to systematically review whether the presence of altered central pain modulation pre-surgical influences outcome after total knee replacement (TKR) in patients with knee osteoarthritis (OA), and if so which indices of central pain modulation predict poor outcome after TKR. To identify relevant articles, PubMed and Web of Science were searched. The search strategy was a combination of key words related to "Knee Osteoarthritis and Total Knee Replacement", "Central Pain Modulation" and "Post-Surgical Outcome Measures". Articles fulfilling the inclusion criteria were screened for methodological quality and results were analyzed and summarized. Sixteen prospective cohort studies were included. Strong evidence is available that presence of catastrophic thinking and poor coping strategies predict more pain after TKR and that there is no association between fear of movement and post-surgical pain or function. Evidence on other psychosocial influences is limited or conflicting. Literature on the influence of other signs of altered central pain modulation on post-surgical outcome is scarce. It is plausible that pre-surgical signs of altered central pain modulation, such as joint pain at rest or widespread pain sensitization, predict more post-surgical pain. Surgeons should be attentive for patients with signs of altered central pain modulation before surgery as they might be at risk for unfavorable outcome. A broader therapeutic approach aiming to desensitize the central nervous system can be adapted in these patients. Further research is however needed to identify the influence of central pain modulation pre-surgical in predicting outcome after TKR.